Lightweight tubular fiberboard: Effect of hole diameters and number on panel properties - Khakzad, Javad; Shalbafan, Ali; Kazemi-Najafi, Saeed (Maderas. Ciencia y Tecnología, 2020)
Special tubular fiberboard with a density of 550 kg/m3 was manufactured using the round rods for creation of the holes. Physicomechanical properties of tubular fiberboard (6, 8, 10, 12 (mm)) with various hole diameters and number of hole (0, 1, 2 and 3 in a constant cross section) were evaluated. The surface layers density, especially on top of the holes, considerably elevated with increasing the hole diameter. This did create higher bending properties as well as higher internal bond and surface soundness. The structure of webs between the holes, when the holes’ number increases, were predominant factor influencing the panel properties. Weak and loose web structure were obtained by increasing the holes’ number from 1 to 3 within a constant cross section (50 mm × 16 mm) that was due to the less transferred fiber during pressing in the webs’ sections. A corresponding comparison of panel properties with those in American and European standards presents that the minimum requirements according to most of the standards (ANSI A208/2, EN 14755, EN 312/P2 and EN 622-5/P1) were obtained.